Inflammatory Bowel Diseases and Nephropathies: Exploring the Gut–Kidney Axis - Roberto de Sire; Alessia La Mantia; Livio Bonacci; Anna Testa; Alessia Dalila Guarino; Antonio Rispo; Olga Maria Nardone; Fabiana Castiglione (Life)
Inflammatory bowel disease (IBD) can extend beyond the gastrointestinal tract, affecting extraintestinal organs and significantly increasing morbidity and mortality. Despite early studies revealing kidney involvement in nearly a quarter of patients with IBD, renal manifestations have been notably overlooked. Among these manifestations, nephrolithiasis, obstructive uropathy, and fistula formation between the bowel and urinary tract are the most reported occurrences. Additionally, renal parenchymal involvement in IBD, including glomerulonephritis (GN), tubulointerstitial nephritis, and amyloidosis, has been documented. GN is particularly noteworthy, as a significant proportion of patients progress to end-stage kidney disease (ESKD). Although GN has long been recognized as a potential extraintestinal manifestation (EIM) of IBD, it has often been dismissed as an anecdotal association. Recently, several studies highlighted the clinical correlation between GN and IBD, suggesting a pathogenic interplay involving gut inflammation, dysbiosis, and intrinsic glomerular processes. Thus, our objective is to elucidate the basis of IBD-related nephropathies, with a specific focus on IgA nephropathy (IgAN) and the gut–kidney axis.